Development of an led array for dosimetry in diagnostic radiology - Damulira, Edrine (2021)
The first goal of this research is to explore the dosimetric response of surface mount device (SMD) light-emitting diodes (LEDs) to diagnostic X-rays and radiotherapy beams. The response to diagnostic X-rays was examined using five LED strips colors based on variable diagnostic X-ray parameters, including kilovoltage peak (kVp), tube current-time product (mAs), dose, and source to detector distance. The response to radiotherapeutic beams was preliminarily investigated with a cold white LED, while varying the irradiation angle, beam energy, source-surface distance, field size, and absorbed dose. This work’s second objective is to amplify diagnostic X-ray radiation-induced signals by increasing the number of LED chips and using an amplifier board. Additionally, a detection capability comparison between the cold white LED and a bpw43 photodiode is presented. Finally, this investigation aims at designing and fabricating an LED array prototype (LAP) dosimetric system. The LAP comprises a 20 × 20 cm2 array of photovoltaic cold white LED chips sandwiched between two intensifying screens. The system was placed inside an air cavity shielded from optical noise using black vinyl tape. The screens converted diagnostic X-ray beams to fluorescent blue light. The LEDs herein were executed in detector mode; thus, they converted the fluorescent light into radiation-induced currents. These analog currents were quantified and converted into digital voltage signals using a digital multimeter. LAP characterization was implemented with (i) beam qualities established by the IEC 61267, i.e., RQR 7 (90 kVp) and RQR 8 (100 kVp), and (ii) low (25 mAs) and high (80 mAs) beam quantities defined herein. The cold white LED demonstrated a better dosimetric behavior. LED chip number increment produced higher amplification coefficients than the amplifier board. Both the photodiode and LEDs demonstrated similar signal precision, linearity to mAs (dose), and dose and energy dependence. The minimum dose detected by the LAP was 0.1386 mGy, whereas the maximum dose implemented here was ~ 13 mGy. Whereas the LAP absorbed dose linearity was 99.18 %, mAs linearity was 98.64 %. The sensitivity of the system fluctuated by ± 4.69 %, ± 6.8 %, and ± 7.7 % during energy, dose, and dose rate variation, respectively. Two LAP data sets were 89.93 % repeatable. Thus, this study proposed an ultrathin (5 mm), lightweight (130 g), and relatively low cost (US $255) LED-based dosimetric prototype system. This prototype’s dosimetric mechanism was simple, efficient, and accurate.